Accrual Accounting Compliance Drivers: An Indonesian Public Sector Study - Ashari, Mokhamad Meydiansyah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The transition to accrual accounting in the public sector is widely considered essential for improving financial transparency, accountability, and management efficiency. However, its implementation presents significant challenges, particularly in developing countries. Specific Background: Indonesia's transition to accrual accounting, mandated by Government Regulation 71 of 2010, aimed to enhance financial reporting but has faced persistent compliance issues. Knowledge Gap: Despite the theoretical advantages of accrual accounting, empirical research on the factors influencing compliance, particularly in the Indonesian public sector, remains limited. Existing studies often rely on small sample sizes and qualitative approaches, leaving a gap in comprehensive, data-driven analyses. Aims: This study investigates the key drivers of compliance with accounting standards in Indonesian public sector institutions, focusing on audit opinions as a compliance proxy. Methods: A mixed-methods approach was employed, combining survey responses, structured interviews, focus group discussions, and panel data analysis using an ordered probit regression model. Results: Adoption time was the most significant factor influencing compliance, with institutions requiring at least five years for full adaptation. Contrary to expectations, central government entities exhibited lower compliance than local governments. Regional factors and resource dependency showed no significant impact. Novelty: This study bridges methodological gaps by integrating quantitative and qualitative data, offering a holistic perspective on compliance determinants. Implications: Policymakers should allow extended implementation timelines, tailor support mechanisms for different government levels, and prioritize long-term capacity building over immediate compliance benchmarks. The findings provide valuable insights for developing countries undergoing similar public sector accounting reforms.